Histological, Histometrical and Hormonal Assay ComparativeStudy of Thyroid Glands between Suckling and Adult Local Male Cats (Felis catus) - Diyar Mohammad Hussein; Iman Mousa Khaleel (University of Thi-Qar Journal of agricultural research, 2024)
The present study was amid to describe on histological, histometric and hormonal assay characteristics of the thyroid glands in suckling and adult local male cats(Felis catus)appeared the healthy. The study was conducted on ten suckling (5) and adult (5) local male cats. The histological structural of thyroid gland in suckling and adult cats was similarstatistical all histological measurements of left lobe in suckling and adult cats were higher significantly than those of the right one. The thickness of capsule, diameter of large, medium, small follicle and height of epithelium histological measurements of right and left thyroid lobes in adult cats were higher significantly then those in suckling at p <0.05. these variations in may be due to the differences of studied cats.